Influence of Pesantren Da'wah in the Digital Space: An Examination of the Peaceful Da'wah by Lora Ismael Al-Kholili - Fathoni, Akhmad Yazid (Journal of Pesantren and Diniyah Studies, 2024)
Religious moderation is one of the key philosophies underpinning Indonesian society's lives. However, with the advancement of technology, many seeds of propaganda and intolerant preaching in the name of religion have emerged on social media. This phenomenon potentially threatens Indonesians' understanding of religious moderation. Currently, there are not many influencers, particularly from the pesantren community, who dare to promote moderate Islam on social media. This research aims to examine the methods and role of Ismael al-Kholilie in spreading peaceful da'wah on Instagram. This study employs a qualitative method with descriptive analysis. The findings presented an analytical description of the content, combined with discourse analysis theory on social media related to Lora Ismael's da'wah activities. This research study uses Alvin L. Bertran's role theory. The results of this research reveal that with the peaceful da'wah methods applied by Lora Ismael al-Kholilie, he has made a significant contribution to nurturing the understanding of moderation in Indonesian society. By packaging da'wah concepts and methods into a narrative, the messages Lora Ismael wishes to convey become more impactful and captivating to readers, making them more readily accepted.